TGFβ‐TAZ/SRF signalling regulates vascular smooth muscle cell differentiation. (20th April 2017) - Pagiatakis, Christina; Sun, Dandan; Tobin, Stephanie W.; Miyake, Tetsuaki; McDermott, John C.
Abstract : Vascular smooth muscle cells (VSMCs) do not terminally differentiate; they modulate their phenotype between proliferative and differentiated states, which is a major factor contributing to vascular diseases. TGFβ signalling has been implicated in inducing VSMC differentiation, although the exact mechanism remains largely unknown. Our goal was to assess the network of transcription factors involved in the induction of VSMC differentiation, and to determine the role of TAZ in promoting the quiescent VSMC phenotype. TGFβ robustly induces VSMC marker genes in 10T1/2 mouse embryonic fibroblast cells and the potent transcriptional regulator TAZ has been shown to retain Smad complexes on DNA. Thus, the role of TAZ in regulation of VSMC differentiation was studied. Using primary aortic VSMCs coupled with siRNA‐mediated gene silencing, our studies reveal that TAZ is required for TGFβ induction of smooth muscle genes and is also required for the differentiated VSMC phenotype; synergy between TAZ and SRF, and TAZ and Myocardin (MyoC856), in regulating smooth muscle gene activation was observed. These data provide evidence of components of a novel signalling pathway that links TGFβ signalling to induction of smooth muscle genes through a mechanism involving regulation of TAZ and SRF proteins. In addition, we report a physical interaction of TAZ and MyoC856. These observations elucidate a novel level of control of VSMC induction which may have implications for vascular diseases and congenital vascular malformations. Abstract : The canonical TGFβ pathway is required for the activation of smooth muscle gene expression through the combination of downstream effectors including TAZ, myocardin and SRF. Our data suggest that TAZ not only regulates myocardin transcription but also physically interacts with MyoC856 to promote SRF activation of smooth muscle‐specific genes.